Digitalization of The Formation and Testing of Laws and Regulations In Indonesia - Mastorat Mastorat; Atma Suganda; Md. Shodiq (Jurnal Indonesia Sosial Sains, 2024)
This research was conducted to examine how efforts to digitize the formation and also test the laws and regulations in Indonesia. Where the Ministry of Law and Human Rights as an institution representing the government in the formation of laws and regulations through the Directorate General of Laws and Regulations launched a digitalization program for the formation of laws and regulations to make it easier for the public to participate in the formation of laws and regulations because it is equipped with five innovations, namely e-public participation, e-invitation, e-litigation, Design HelpDesk, Design Chat Podcast (OPERA). Meanwhile, in terms of legal review, the Constitutional Court as a judicial institution tasked with maintaining the constitution and democracy and protecting human rights so that they can be easily recognized by the Indonesian people through digital technology tools so that the Indonesian people can not only easily know the Constitutional Court but also can easily submit applications or lawsuits to the Constitutional Court if they experience constitutional losses, namely through www.mahkamahkonstitusi.go.id website. With the efforts to digitize the formation and testing of these laws and regulations, it is expected that the public will be more active in participating in the formation and testing of laws and regulations